Carbon capture in coffee production systems in the department of Nariño - Manchabajoy Cañar , Juan Pablo; Andrade Díaz, Danita; Castillo Marín , Álvaro José (Ciencia y Agricultura, 2022)
One of the biggest environmental problems that has affected the planet is global warming, due to high concentrations of carbon (CO2), this has led to crops such as coffee being affected by climate change caused by greenhouse gases (GHG), especially due to the increase in the incidence of pests and diseases. However, carbon capture contributes to the mitigation of GHG emissions. The objective of this work was to evaluate the carbon stored in the above-ground and underground biomass in four six-year-old castle coffee production systems. In a trial established under Random Complete Blocks Design (DBCA) with the treatments Coffee to free exposure (T1), Coffee-Limón (T2), Coffee-Guamo (T3) and Coffee-Carbonero (T4), in three altitudes: less than 1550 meters above sea level, between 1550 and 2000 meters above sea level and above 2000 meters above sea level. Data corresponding to stem diameters were taken in coffee seedlings and shade trees with which allometric equations were applied to obtain the carbon variables in the aerial and root biomass and the carbon variables in litter and soil obtained from their dry material. Highly significant differences were obtained in the 4 evaluated treatments, being T4 the one with the highest concentration of carbon in the soil biomass with 100.14 t ha-1 and in the aerial biomass with 190.42 t ha-1.